Effectiveness Of Virtual Recruitment – A Study On Commerce And Managment Students’ Perspective (Journal of Namibian Studies : History Politics Culture, 2023)
The effects of Covid-19 on corporate procedures, especially hiring, may be seen all over the world. Companies need to promptly and imaginatively alter their recruitment strategies in response to the epidemic. Businesses are reconsidering their hiring practices and shifting to remote work to mitigate the health hazards posed by the epidemic. Numerous companies have successfully made the transition from traditional recruiting methods to online platforms by implementing the necessary technological infrastructure. The trend toward virtual recruiting, which emerged in response to the recession, is gaining popularity. Some of the most important online recruiting strategies are online job portals, corporate career directories, data processing, candidate monitoring systems, business internal job posting platforms, social recruitment, smartphone recruitment, video conference conferences, and online examination, all of which have a significant impact on the recruitment process and on job-seekers in general. This study's overarching objective is to learn what makes Virtual Recruitment procedures successful from the applicants' point of view. An organized questionnaire was used to compile the descriptive data for this investigation. The survey's 18 questions were divided into five categories based on the results of a literature analysis spanning from 1999 to 2020: perceived effectiveness, user friendliness, information distribution, perceptions of objectivity, and firm perceptions. Convergent and discriminant validity were used to confirm the validity and reliability of the questionnaire's scales. Cochran's method for an unknown population with 95% confidence and 10% margin of error led to the selection of a sample size of 110 respondents. According to the study's results, potential commerce and management job seekers are enthusiastic about virtual recruiting platforms and consider ease of use to be the most important factor in determining a platform's efficacy. The recent outbreak has renewed interest in this oft-repeated saying. The modern worker is more resilient and prepared to make the best of any situation, no matter how trying it may be. Technological progress has made it possible for businesses to rapidly adopt a virtual recruiting procedure, opening the door to a hybrid recruitment approach in the near future.